Joint Raman spectroscopic and quantum chemical analysis of the vibrational features of Cs2RuO4. (28th April 2015) - Naji, M.; Di Lemma, F.; Kovács, A.; Beneš, O.; Manara, D.; Colle, J.‐Y.; Pagliosa, G.; Raison, P.; Konings, R. J. M.
<x xml:space="preserve">Abstract</x> The Raman spectroscopic characterization of the orthorhombic phase of Cs2RuO4 was carried out by means of group theory and quantum chemical analysis. Multiple models based on ruthenate (VI+) tetrahedra were tested, and characterization of all the active Raman modes was achieved. A comparison of Raman spectra of Cs2RuO4, Cs2MoO4, and Cs2WO4 was also performed. Raman laser heating induced a phase transition from an ordered to a disordered structure. The temperature‐phase transition was calculated from the anti‐Stokes/Stokes ratio and compared with the ones measured at macroscopic scale. The phase transition is connected with tilting and/or rotations of RuO4 tetrahedra, which lead to a disorder at the RuO4 sites. Copyright © 2015 John Wiley & Sons, Ltd.